Multilocus genotypes and broad host-range of Enterocytozoon bieneusi in captive wildlife at zoological gardens in China. Issue 1 (December 2016) - Li, Wei; Deng, Lei; Yu, Xingming; Zhong, Zhijun; Wang, Qiang; Liu, Xuehan; Niu, Lili; Xie, Na; Deng, Jiabo; Lei, Shuangshuang; Wang, Liqin; Gong, Chao; et al.
Abstract Background Enterocytozoon bieneusi is a common opportunistic pathogen that is widely detected in humans, domestic animals and wildlife, and poses a challenge to public health. The present study was performed to evaluate the prevalence, genotypic diversity and zoonotic potential ofE. bieneusi among wildlife at Chengdu and Bifengxia zoological gardens in Sichuan Province, China. Results Of the 272 fresh fecal samples harvested from 70 captive wildlife species at Chengdu Zoo (n  = 198) and Bifengxia Zoo (n  = 74), 21 (10.6 %) and 22 (29.7 %) tested positive forE. bieneusi by internal transcribed spacer (ITS) sequencing analysis, respectively. Specifically, genotypes D, Peru 6, CHB1, BEB6, CHS9, SC02 and SC03, and genotypes D, CHB1, SC01 and SC02 were detected in the Chengdu and Bifengxia Zoo samples, respectively. Five known genotypes (D, Peru 6, BEB6, CHS9 and CHB1) and three novel genotypes (SC01, SC02 and SC03) were clustered into the zoonotic group (group 1) and host-adapted group (group 2). Multilocus sequence typing (MLST) analysis targeting three microsatellites (MS1, MS3 and MS7) and one minisatellite (MS4) were successfully sequenced for 37, 33, 35 and 37 specimens, generating 8, 3, 11 and 15 distinct locus types, respectively. Altogether, we identified 27 multilocus genotypes (MLGs) among theE. bieneusi isolates by MLST. These data highlight the high genetic diversity ofE. bieneusi among zoo wildlife. Conclusions To our knowledge, this is the first report on the prevalence and genotypic diversity ofE. bieneusi infections among captive wildlife in zoos in southwest China. Notably, we identified three novelE. bieneusi genotypes, as well as six new mammalian hosts (Asian golden cats, Tibetian blue bears, blackbucks, hog deer, Malayan sun bears and brown bears) for this organism. Moreover, the occurrence of zoonotic genotypes suggests that wildlife may act as reservoirs ofE. bieneusi that can serve as a source of human microsporidiosis. The findings presented here should contribute to the control of zoonotic disease in China.